2004
DOI: 10.1111/j.1365-2141.2004.05232.x
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose melphalan with autologous stem cell transplantation after VAD induction chemotherapy for treatment of amyloid light chain amyloidosis: a single centre prospective phase II study

Abstract: SummaryAmyloid light chain (AL) amyloidosis is the result of a clonal plasma cell expansion, in which monoclonal light chains transform to amyloid deposit in various tissues and can lead to organ dysfunction and organ failure. The median survival of patients with AL amyloidosis without therapy is 10–14 months. With high‐dose melphalan (HDM) and autologous stem cell transplantation (ASCT), haematological and clinical remission rates of up to 50% of treated patients have been reported from phase II studies. HDM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
7

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(51 citation statements)
references
References 27 publications
(39 reference statements)
0
44
0
7
Order By: Relevance
“…This practice is the custom in many of the European countries that perform stem cell transplantation. 20,21 Other investigators have also questioned whether postinfusion G-CSF administration has a clear financial benefit. 22 We demonstrated that in amyloidosis, it is also possible to perform stem cell transplantation as an outpatient procedure; however, the majority of patients who receive the transplant do require hospitalization (the median stay is 9 days).…”
Section: Discussionmentioning
confidence: 99%
“…This practice is the custom in many of the European countries that perform stem cell transplantation. 20,21 Other investigators have also questioned whether postinfusion G-CSF administration has a clear financial benefit. 22 We demonstrated that in amyloidosis, it is also possible to perform stem cell transplantation as an outpatient procedure; however, the majority of patients who receive the transplant do require hospitalization (the median stay is 9 days).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous reports have described the availability of autologous PBSCT for systemic AL amyloidosis, but some reviews have reported high TRMs (13-39%) in autologous PBSCT for systemic AL amyloidosis [2][3][4][5][6][7]. Comenzo and Gertz [4] described TRM rates approaching 100% in patients with cardiac amyloidosis and clinical congestive heart failure or history of arrhythmia, syncope, or recurrent pleural effusion.…”
Section: Discussionmentioning
confidence: 99%
“…Less than 5% of all patients with systemic AL amyloidosis survive !10 years from the time of diagnosis. Several recent studies have reported the efficacy of autologous peripheral blood stem cell transplantation (PBSCT) for patients with systemic AL amyloidosis [2][3][4][5][6][7]. However, PBSCT can only be offered to a small proportion of patients, due to the high transplantrelated mortality (TRM), particularly in patients with cardiac amyloidosis.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] High-dose therapy with auto-SCT (HDT-ASCT) has been shown to be associated with long-term survival in AL patients. [11][12][13][14][15] However, high TRM ranging from 13 to 43%, especially in patients with cardiac involvement, questions the applicability of this treatment modality. 16 In order to answer this question, we performed a retrospective analysis of AL patients with cardiac involvement undergoing HDT-ASCT at our center.…”
Section: Cardiac Involvement In Patients With Light-chain Amyloidosismentioning
confidence: 99%